Numerical Simulation of Permeability Change in Wellbore Cement Fractures after Geomechanical Stress and Geochemical Reactions Using X-ray Computed Tomography Imaging - Kabilan, Senthil; Jung, Hun Bok; Kuprat, Andrew P; Beck, Anthon N; Varga, Tamas; Fernandez, Carlos A; Um, Wooyong (Environmental science & technology, 2016)
X-ray microtomography (XMT) imaging combined with three-dimensional (3D) computational fluid dynamics (CFD) modeling technique was used to study the effect of geochemical and geomechanical processes on fracture permeability in composite Portland cement-basalt caprock core samples. The effect of fluid density and viscosity and two different pressure gradient conditions on fracture permeability was numerically studied by using fluids with varying density and viscosity and simulating two different pressure gradient conditions. After the application of geomechanical stress but before CO2-reaction, CFD revealed fluid flow increase, which resulted in increased fracture permeability. After CO2-reaction, XMT images displayed preferential precipitation of calcium carbonate within the fractures in the cement matrix and less precipitation in fractures located at the cement-basalt interface. CFD estimated changes in flow profile and differences in absolute values of flow velocity due to different pressure gradients. CFD was able to highlight the profound effect of fluid viscosity on velocity profile and fracture permeability. This study demonstrates the applicability of XMT imaging and CFD as powerful tools for characterizing the hydraulic properties of fractures in a number of applications like geologic carbon sequestration and storage, hydraulic fracturing for shale gas production, and enhanced geothermal systems.